2011
DOI: 10.1007/s12105-011-0248-0
|View full text |Cite
|
Sign up to set email alerts
|

Myocbacterium-Avium Intracellulare Associated Inflammatory Pseudotumor of the Anterior Nasal Cavity

Abstract: In this case report, we describe an unusual case of mycobacterial associated inflammatory pseudotumor that occurred in a patient with a previous history of cocaine abuse. We discuss inflammatory pseudotumor (IPT) in general and emphasize the rare entity where an associated mycobacterial infection is seen. The histogenesis is not yet completely understood. The lesion can pose challenges for practicing pathologists and a misdiagnosis of malignancy can occur at multiple facets. A discussion about the differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…Middleton et al [16] showed exposing extracellular matrix by epithelial damage and poor mucus clearance will predispose to MAC airway infection. Previously reported cases of nasal and sinobronchial infections of MAC included history of cocaine use and long term aerosol inhalation cine-scintigraphy usage, which suggested that an impairment of the local defense mechanisms may play role in the pathogenesis of MAC infection [3,17]. Solyar et al reported thirty-seven Atypical mycobacterium (AM) associated chronic refractory rhinosinusitis (CRS) cases, which accounts for 5.3 % of outpatients and 2.6 % of OR patients with CRS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Middleton et al [16] showed exposing extracellular matrix by epithelial damage and poor mucus clearance will predispose to MAC airway infection. Previously reported cases of nasal and sinobronchial infections of MAC included history of cocaine use and long term aerosol inhalation cine-scintigraphy usage, which suggested that an impairment of the local defense mechanisms may play role in the pathogenesis of MAC infection [3,17]. Solyar et al reported thirty-seven Atypical mycobacterium (AM) associated chronic refractory rhinosinusitis (CRS) cases, which accounts for 5.3 % of outpatients and 2.6 % of OR patients with CRS.…”
Section: Resultsmentioning
confidence: 99%
“…Acid fast stain and PAS stain highlighted numerous short, uniformly staining coccobacilli within the foamy histiocytes (Figs. 3,4). The sheet of foamy histiocytes are strongly positive for CD68 (Fig.…”
Section: Case Reportmentioning
confidence: 96%
See 2 more Smart Citations
“…As a cause of focal or multifocal cutaneous and/or subcutaneous infection, MAC members can initiate three morphological forms of inflammatory response in infected cats: granulomatous, pyogranulomatous or spindle cell granulomas (Lee Gross et al, 2010). In human medicine, proliferation of spindle-shaped histiocytes containing acid-fast mycobacteria occurs as an inflammatory response to both tuberculous and nontuberculous mycobacteria (Ilyas et al, 2011). These benign lesions are referred to as mycobacterialinduced inflammatory 'pseudotumour' (IPT) and are described rarely.…”
mentioning
confidence: 99%